2015
DOI: 10.1007/s12010-015-1676-1
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial Sunscreen Scytonemin: Role in Photoprotection and Biomedical Research

Abstract: Cyanobacteria are the most promising group of photosynthetic microorganisms capable of producing an array of natural products of industrial importance. Scytonemin is a small hydrophobic alkaloid pigment molecules present in the extracellular sheath of several cyanobacteria as a protective mechanism against short wavelength solar ultraviolet (UV) radiation. It has great efficacy to minimize the production of reactive oxygen species and formation of DNA lesions. The biosynthesis of scytonemin is regulated by dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(63 citation statements)
references
References 55 publications
2
61
0
Order By: Relevance
“…Structurally, in their formation nitrogen substituent of amino acids and cyclohexenimine or cyclohexenone chromophore conjugated with one or two amino acids is involved, having absorption maxima ranging from 310 to 362 nm (Singh et al, 2008; Bhatia et al, 2011). MAAs are produced in several cyanobacteria, rhodophyta, and several other groups of microalgae (Sinha et al, 2007; Carreto and Carignan, 2011; Rastogi et al, 2015; Rastogi and Madamwar, 2016). They have absorption maxima in UV range (Takano et al, 1979; Bhatia et al, 2011; Kannaujiya et al, 2014).…”
Section: An Outlook Of Metabolites: Basically What They Are?mentioning
confidence: 99%
“…Structurally, in their formation nitrogen substituent of amino acids and cyclohexenimine or cyclohexenone chromophore conjugated with one or two amino acids is involved, having absorption maxima ranging from 310 to 362 nm (Singh et al, 2008; Bhatia et al, 2011). MAAs are produced in several cyanobacteria, rhodophyta, and several other groups of microalgae (Sinha et al, 2007; Carreto and Carignan, 2011; Rastogi et al, 2015; Rastogi and Madamwar, 2016). They have absorption maxima in UV range (Takano et al, 1979; Bhatia et al, 2011; Kannaujiya et al, 2014).…”
Section: An Outlook Of Metabolites: Basically What They Are?mentioning
confidence: 99%
“…Scytonemin is able to reduce up to 90% of UV-A radiation into the cells due to its excellent absorption in this UV range [78][79][80]. It also absorbs in the UV-B range [81,82].…”
Section: Scytoneminmentioning
confidence: 99%
“…Fleming & Castenholz (2008) studied the effects of nitrogen source (N 2 , NO 3 − or NH 4 + ) on scytonemin synthesis in Nostoc punctiforme, showing that this cyanobacterial species synthesized three to seven times more scytonemin while fixing nitrogen than when utilizing nitrate or ammonium. The exact mechanisms of scytonemin induction are unclear but multiple environmental signals may act to determine the level of this pigment in different species of cyanobacteria (Rastogi et al, 2015).…”
Section: Scytoneminmentioning
confidence: 99%
“…Recently, Malla & Sommer (2014) generated the monomer moiety of scytonemin from tryptophan and tyrosine in Escherichia coli and discovered that only three enzymes are required for its in vivo production. The precise mechanism of scytonemin biosynthesis is still ambiguous, however, recent studies indicated that biosynthesis of this pigment in cyanobacteria is a highly conserved process (Rastogi et al, 2015). Wada et al (2013) proposed a pathway for scytonemin synthesis in cyanobacteria in which enzymes ScyA, B and C are assumed to catalyse the synthesis of scytonemin monomers, while ScyC, D and F are assumed to catalyse the dimerization of the subunits (Fig.…”
Section: Scytoneminmentioning
confidence: 99%
See 1 more Smart Citation